Kabuki plays on stage (University of Hawai'i Press, 2002)
This volume two in a monumental new series -- the first collection of kabuki play translations to be published in nearly a quarter of a century. Drawing on new research in kabuki performance and history, these translations of traditional plays are the work of twenty-two scholars, ranging from the most eminent in the field to younger scholars for whom kabuki is both an academic and personal passion. Published in four volumes, the series vividly traces kabuki's changing relations to Japanese society during the premodern era.